2010
DOI: 10.1111/j.1741-3729.2010.00589.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Parents' Self‐Blame in Relation to Adolescents' Mental Disorders

Abstract: This study examined whether parents of adolescents diagnosed with mental disorders self‐blame for their child's disorders; their reasons for self‐blame; and the relationships between parental self‐blame and lower psychological well‐being, perceived stigmatization, social support, potential hereditary factors related to adolescents' mental disorders, demographics, and youths' clinical characteristics. Analysis of qualitative and quantitative interview data was used to classify 68 parents as “more” or “less” (40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
1
13

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(97 citation statements)
references
References 66 publications
3
80
1
13
Order By: Relevance
“…This pattern can be explained via different mechanisms; for instance, through parental worries about the present (e.g., meeting daily demands in school) and future (e.g., occupation potential) of their child [31]; and through parental feelings that they are to blame for their child's mental disorder [47]. Furthermore, the impact on parents could be heightened because these children need more support (e.g., doing homework), which leads to less free time for the parents, less time the parents have available for other family members, and their need for greater organizational effort to balance the child's care and parents' work [48].…”
Section: Parent Ratingsmentioning
confidence: 99%
“…This pattern can be explained via different mechanisms; for instance, through parental worries about the present (e.g., meeting daily demands in school) and future (e.g., occupation potential) of their child [31]; and through parental feelings that they are to blame for their child's mental disorder [47]. Furthermore, the impact on parents could be heightened because these children need more support (e.g., doing homework), which leads to less free time for the parents, less time the parents have available for other family members, and their need for greater organizational effort to balance the child's care and parents' work [48].…”
Section: Parent Ratingsmentioning
confidence: 99%
“…Mental health problems are, among other conditions, prevalent in this age group due to the early onset of many disorders [3][4][5][6][7]. Such problems also account for a large proportion of the disease burden in young people [7,8], compromise various quality of life domains [9] and exert an additional impact upon parents (e.g., experiencing stigma or self-blame) [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…As previously noted, the parents in the study clearly experienced significant self-blame for their child's illness. In a study of parental self-blame, Moses (2010b) found that 60% of the 70 caregiver sample felt fully or partially responsible for their adolescents' Similarly, a process occurred in this present research where parent blame morphed into staff blame.…”
Section: Principal Theme 3: Ubiquitous Painmentioning
confidence: 87%
“…This suggests that a role for teams could be to act as a reflexive sounding board for parents who are usually in a state of anxious confusion about their child's well-being. By doing so, teams have the opportunity to challenge some of the myths of mental illness with the parents while at the same time addressing their own biases and assumptions (Moses, 2010b). Geraghty et al's (2011) study of 50 caregiver experiences also revealed that when staff took the time to respond to parent needs, frustration and stress were considerably reduced.…”
Section: The Importance Of Reflexivity In the Teammentioning
confidence: 99%
See 1 more Smart Citation